Foreword - EPURE, Manuela (Journal of Economic Development, Environment and People, 2016)
The world economy is still recovering after the ‘big crisis’, whose effects are visible in many industries, thus making the investors more cautious about new projects. At the regional level, the European Union has developed an ambitious strategy for the coming decades. EU’s growth plan aims to deliver a smart, sustainable and inclusive growth, focused on five goals in the areas of employment, education, innovation, poverty reduction and climate/energy.